Teasing Paradoxes to Explore Transformative Futures of Peace - Heinonen, Sirkka; Pättikangas, Paula; Viitamäki, Riku; Taylor, Amos (Tamkang University, 2025)
This paper discusses the outcome of a methodologically innovative foresight exercise. A Futures Clinique was conducted to address paradoxes of peace. For the purpose, a novel method of p'aradox probing' was launched where paradoxes are employed as tools for sense-making for future developments concerning complex issues. Various paradoxes around peace were identified and compared. The results as thematically analysed show us the necessity of constructing preferred futures amidst pressing global challenges and tensions. Such a preferred future is positive peace and implications it encompasses. Further efforts will be made to relate the present-day paradoxes closely to futures contexts.